The mother - child nexus. Knowledge and valuation of wild food plants in Wayanad, Western Ghats, India - Cruz García Gisella (BMC, 2006)
Abstract This study focuses on the mother-child nexus (or process of enculturation) with respect to knowledge and valuation of wild food plants in a context where accelerated processes of modernization and acculturation are leading to the erosion of knowledge and cultural values associated with wild food plant use, in Wayanad, Western Ghats, India. Wild food plants in this biodiversity hotspot form an important part of local diets and are used as famine foods and medicines. In general, the collection and consumption of these foods are increasingly stigmatized as symbols of poverty and 'tribalness' (equivalent to 'backwardness'). The study, which falls within the discipline of ethnobotany, involves three socio-cultural groups - the Paniya and Kuruma tribes and non-tribals. Further, it examines the impact in the enculturation process of an unusual educational programme sponsored by the MS Swaminathan Research Foundation that is oriented towards creating awareness among children of cultural identity and local biological resources - the study compares children having participated in the programme with those who have not, with their mothers. The process of enculturation is assessed by comparing wild food plant knowledge and values between mothers and their children, and by examining events where knowledge transmission occurs, including collection and consumption. For that, quantitative and qualitative data collection and analysis tools were used, and methods included semi-structured interviews, photo identification and informal interviews of key informants. Results ratify that women are the knowledge holders and are the primary means of knowledge transmission to their children. Nevertheless, fewer children are collecting wild food plants with mothers and learning about them, apparently because of children's lack of time. On the other hand, older people acknowledge that a "change in taste" is occurring among younger generations. In general, there is a simultaneous transmission from mothers to children of contrasting values pertaining to wild food plants: that they are 'good food' but also that they are symbols of low status and poverty, leading to feelings of shame and inferiority. Finally, the study concludes that the educational programme, through a "learning by doing" approach counteracts social stigma and encourages learning among children of all ages and socio-cultural groups, particularly stimulating non-tribal children to learn from tribals.